Russian and American Armed Forces: A Comparison with Questions Summary - Tchantouridzé, Lasha (Politics / პოლიტიკა; 2018: პირველი ნომერი, 2018)
In November-December 2017, the CRRC Georgia, in cooperation with the National Democratic Institute (NDI) conducted a public opinion poll in the Republic of Georgia. Among the questions was one asking the respondents to compare military strength of Russia with that of the United States. Forty-one percent of the respondents identified Russia as stronger than the US, 36% thought that the US forces were stronger, 15% assessed them at equal strength, and 8% responded with "do not know." The answer distribution appears to be baffling, but in fact, all of them are correct. When it comes to the strategic arms, the United States and the Russian Federation are maintaining parity, as this is the most desirable state of affairs when it comes to nuclear weapons. The United States has more experience and success when it comes to expeditionary warfare, while the Russian Federation has enjoyed more success in wars with its neighboring states. Given such a mixed recent record, "do not know" and "it depends" answers would also be correct. This was not the only question without limited boundaries in the CRRC questionnaire: the set of questions on the foreign propaganda (q11, q13 and q15) were similarly open-ended.